2009
DOI: 10.1021/jp903240v
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Structures of cis- and trans-1,2-Dichloroethylene in Supercritical CO2 Investigated by Raman Spectroscopy and Attractive Energy Calculations

Abstract: Vibrational Raman spectra of the C horizontal lineC stretching modes of cis- and trans-1,2-dichloroethylene (C(2)H(2)Cl(2)) were measured in supercritical carbon dioxide (CO(2)). The spectra were collected at a fixed solute mole fraction by varying the fluid density by a factor of 20. As the density increased, the peak frequencies of the C horizontal lineC stretching modes shifted toward the low-energy side at isotherms of reduced temperature, T(r) = T/T(c) = 1.02, 1.06, and 1.20. By analyzing these density de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…We have investigated supercritical fluid structures with respect to diffusive, rotational, and vibrational motion using dynamic light scattering, terahertz (THz) absorption, , and Raman spectroscopy, , respectively. These studies have been extended to nanomaterial fabrication. In particular, the local structure around solute molecules has been quantified for various systems using Raman spectroscopy and by theoretical analysis, whereby the attractive and repulsive energies of the solute–solvent interactions are investigated as a function of the fluid density to determine various specific properties and structures. , For instance, supercritical Xe, a nonpolar fluid, exhibits the highest attractive energy according to studies on the cis and trans isomers of 1,2-dichloro­ethylene in Xe compared with other supercritical fluids such as CO 2 , CHF 3 , and SF 6 . The attractive energy of a nonpolar trans isomer is higher than that of the polar cis isomer, which is attributed to the isotropic and/or anisotropic molecular distribution and orientation .…”
Section: Introductionmentioning
confidence: 99%
“…We have investigated supercritical fluid structures with respect to diffusive, rotational, and vibrational motion using dynamic light scattering, terahertz (THz) absorption, , and Raman spectroscopy, , respectively. These studies have been extended to nanomaterial fabrication. In particular, the local structure around solute molecules has been quantified for various systems using Raman spectroscopy and by theoretical analysis, whereby the attractive and repulsive energies of the solute–solvent interactions are investigated as a function of the fluid density to determine various specific properties and structures. , For instance, supercritical Xe, a nonpolar fluid, exhibits the highest attractive energy according to studies on the cis and trans isomers of 1,2-dichloro­ethylene in Xe compared with other supercritical fluids such as CO 2 , CHF 3 , and SF 6 . The attractive energy of a nonpolar trans isomer is higher than that of the polar cis isomer, which is attributed to the isotropic and/or anisotropic molecular distribution and orientation .…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy has been used to identify structural differences, typically to differentiate isomeric pairs by taking advantage of changes in select vibrational modes . Notable examples are the work of Yenagi, et al , who used Raman spectroscopy coupled with density functional theory (DFT)‐based theoretical calculations to describe hydrogen bonding and cis‐ isomerism, trans‐ isomerism in 2‐chloro‐3‐hydroxybenzaldehyde and 3‐chloro‐4‐hydroxybenzaldehyde .…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy has been used to identify structural differences, typically to differentiate isomeric pairs by taking advantage of changes in select vibrational modes. [1][2][3][4][5][6] Notable examples are the work of Yenagi, et al, who used Raman spectroscopy coupled with density functional theory (DFT)-based theoretical calculations to describe hydrogen bonding and cis-isomerism, trans-isomerism in 2-chloro-3-hydroxybenzaldehyde and 3-chloro-4hydroxybenzaldehyde. [7] A more recent advancement in Raman spectroscopy presented by Kiefer and Noack detailed a universal method of discriminating enantiomers using polarization resolved Raman spectroscopy with the addition of a half-wave retarder.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the huge number of syntheses that can be carried out in this medium and the renewing interest related to the use of scCO 2 as a green solvent, there is today an increasing demand on the development of efficient and versatile "in situ" techniques for real time monitoring the chemical concentrations. [18,19] In these cases, the laser was incident to the cell, and a camera lens was used to collect the scattered light at an angle of 908. Among these techniques, Fourier infrared spectroscopy and UV spectroscopy under pressure have been used to obtain time-resolved absorption bands evolving during organic reactions and polymerizations.…”
mentioning
confidence: 99%
“…Saitow et al reported on the use of a home-made optical view cell for recording Raman spectra of cis-and trans-C 2 H 2 Cl 2 in supercritical fluids. [18,19] In these cases, the laser was incident to the cell, and a camera lens was used to collect the scattered light at an angle of 908. However, all these experimental devices were only used for studying the solubility of molecules in scCO 2 and not for the online monitoring of reactions.…”
mentioning
confidence: 99%